2020
DOI: 10.1136/rmdopen-2019-001084
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fatigue in Rheumatoid Arthritis

Abstract: Fatigue in rheumatoid arthritis is highly prevalent. It is correlated only weakly with disease activity but more so with pain, mood, personality features, poor sleep, obesity and comorbidities. Fatigue can be measured by many standardised questionnaires and more easily with a Visual Analogue Scale or numeric rating scale. Most patients with RA have some fatigue, and at least one in six have severe fatigue. Chronic pain and depressed mood are also common in RA patients with significant fatigue. It affects funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 79 publications
2
70
2
Order By: Relevance
“…Similarly, also Van Hoogmoed et al (2010), andRepping-Wuts et al (2007) reported that pain, disability, depression, and low self-efficacy were associated with greater fatigue, but inflammatory indices were not correlated with fatigue severity. The fatigue in RA patients may be only partially related to disease activity, which may have accounted for poor agreement with respect to a fatigue domain within a flare questionnaire in RA (Pope, 2020). We found no significant difference in pain intensity and morning stiffness duration between the two study groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, also Van Hoogmoed et al (2010), andRepping-Wuts et al (2007) reported that pain, disability, depression, and low self-efficacy were associated with greater fatigue, but inflammatory indices were not correlated with fatigue severity. The fatigue in RA patients may be only partially related to disease activity, which may have accounted for poor agreement with respect to a fatigue domain within a flare questionnaire in RA (Pope, 2020). We found no significant difference in pain intensity and morning stiffness duration between the two study groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Its pathophysiology is linked to disease activity, persistent pain, sleep deprivation, mood disturbances, other diseases, high inflammatory markers, elevated cytokines, with these a person feel tired or even exhausted similarly to prodrome of an infection. 19 Fatigue has been linked to conventional DMARDs use, specially methotrexate and sulfasalazine, this may contribute to non-adherence to their use, so change in mode of administration and dosing regimen may help. 20,21 Fatigue has severe financial impact leading to very high clinical care costs, increasing consultations, key determinant of sickness, absence and loss of employment, despite of its perceived importance and increased research activity, our understanding for prognostic factors of poor fatigue outcomes is lacking, ultimately poorly managed.…”
Section: Discussionmentioning
confidence: 99%
“…22 Curbing fatigue is possible, by multidimensional approach (non-pharmacologic and pharmacologic) measures, like exercise, cognitive behavioral therapy ,timely and effective use of conventional and biological dmards especially IL-6 blocker (Tocizilumab) and newer medications called conventional synthetic dmards Janus kinase (JAK) inhibitors (tofacinitab, baricinitab),in active, early RA, methotrexate naive, methotrexate and biologics inadequate responders shown major improvements, also treatment of anemia, Vit D and Omega 3 fatty acids supplementation may help. 19…”
Section: Discussionmentioning
confidence: 99%
“…The 23 survey questions were distributed over 14 webpages and divided into 4 domains: socio-demographic and work setting-related characteristics (12), referral to nonpharmacological care (2), treatment (5), and perceived quality of communication (4). The survey included both open-ended questions, asking the participants to answer in their own words, and closed questions, providing multiplechoice and multiple-response questions.…”
Section: Surveymentioning
confidence: 99%
“…In addition, care by health professionals is also based on treatments proven to be effective in other rheumatic diseases. For instance, promising approaches to address fatigue in patients with RA and SLE are also applicable for patients with SSc [12][13][14].…”
Section: Introductionmentioning
confidence: 99%